2023
DOI: 10.1038/s41598-023-33219-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aortic aging using 3D multi-parametric MRI-long-term follow-up in a population study

Abstract: We comprehensively studied morphological and functional aortic aging in a population study using modern three-dimensional MR imaging to allow future comparison in patients with diseases of the aortic valve or aorta. We followed 80 of 126 subjects of a population study (20 to 80 years of age at baseline) using the identical methodology 6.0 ± 0.5 years later. All underwent 3 T MRI of the thoracic aorta including 3D T1 weighted MRI (spatial resolution 1 mm3) for measuring aortic diameter and plaque thickness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These reports are in consistent with our result that the low HIS group tended to be older than the high HIS group. Although the mechanism behind the inferior location of the HIS is not fully understood, it has been reported that with aging, the ascending aorta tends to assume a more horizontal position and enlarge 12,13 . Consequently, the inferior positioning of the HIS may result from the compression of the atria by the aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports are in consistent with our result that the low HIS group tended to be older than the high HIS group. Although the mechanism behind the inferior location of the HIS is not fully understood, it has been reported that with aging, the ascending aorta tends to assume a more horizontal position and enlarge 12,13 . Consequently, the inferior positioning of the HIS may result from the compression of the atria by the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism behind the inferior location of the HIS is not fully understood, it has been reported that with aging, the ascending aorta tends to assume a more horizontal position and enlarge. 12,13 Consequently, the inferior positioning of the HIS may result from the compression of the atria by the aorta. This hypothesis is supported by our finding that the low HIS group exhibited a smaller left atrial diameter.…”
Section: Determinants Of the Location Of The Hismentioning
confidence: 99%